Corporate governance: What is it? - McCabe, Margaret; Nowak, Margaret (Curtin University of Technology, 2007)
The emergence of the phenomenon that has come to be called in modern times, Corporate Governance is described. A selection of corporate governance definitions from the literature is examined. A definition of corporate governance emerging from research data is provided using the language of participating practitioners in governance in Australia. Content analysis was used as the analytical tool in the construction of the definition. The definition-in-use which was the outcome of the analysis is aligned strongly with stakeholder theory.